Risk Factors of Breast Cancer in Patients at Dr. Doris Sylvanus Hospital, Palangka Raya - Mutriqah, Dian Ana; Kania, Nia; Panghiyangani, Roselina; Husaini, Husaini (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2024)
Breast cancer ranks first in contributes to cancer deaths in Indonesia. This study aims to analyze the relationship between menarche age, level of knowledge, and history of the use of control birth pills and the incidence of breast cancer. This study employed a case-control design. Inclusion criteria for the case group were women, 20–50 years, breast cancer patients, junior high education level, and married. The subjects excluded respondents who used contraception. The data comes from questioner and medical record. There were 27 respondents each for the case and control group. The result showed a major age range of 31–40 years (63.0%). The education level was dominated by junior high school (40.7%). The chi-square test showed a correlation between the age of menarche (p = 0.01) OR 5.50 (95% CI: 1.604 -18.864), and knowledge (p = 0.00) OR value of 8.31 (95% CI: 2.437-28.354) with breast cancer, but no correlation between history of use of pills contraception with breast cancer (p = 0.74). The dominant risk factor for breast cancer in patients at Dr. Doris Sylvanus Hospital was the level of knowledge. Increasing knowledge about cancer is important in preventing breast cancer in women, especially in Palangkaraya.